PERAN DAN TANGGUNG JAWAB KONSULTAN HUKUM DALAM KEGIATAN PASAR MODAL - Andre Santika, I Gede; Adi Yaryani, Ni Nengah (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
On the national building program capital market has an important role because capital market is one of alternatives or the means for collecting the funds from society. In capital market mechanism in Indonesian has a supporting profession which is know as the legal consultant. Legal consultant in capital market must be responsible for the legal audit and the legal opinion, where the legal opinion given by the legal consultant will assist the company to get the process of go public. By means of normative method, this paper will give explanation and comprehension concerning the role and the responsibility of a legal consultant in the capital market activity. Where the legal consultant is independent side which is trusted of the skill and the integrity to do the legal audit and give the legal opinion independently to the capital market activity. So based on the skill and the integrity a legal consultant has responsible continually not only to emiten but also to the investor.
Keywords: The Role, The Responsibility, Legal Consultant , Capital Market